Pengaruh Sistem Pengendalian Intern Pemerintah (SPIP) Terhadap Penyerapan Anggaran dengan Mediasi Perencanaan Anggaran dan Moderasi Komitmen Organisasi - Magdalena Renyaan; Agus Utomo; Ridwan Ridwan (Excellent, 2025)
This study aims to analyze the influence of the Government Internal Control System (SPIP) on Budget Absorption by considering Budget Planning as a mediating variable and Organizational Commitment as a moderation variable. This research was conducted in local government agencies with a quantitative approach and used path analysis as a data analysis method with IBM SPSS-Macro Hayes. The results of the study show that SPIP has a significant effect on Budget Absorption, SPIP has an insignificant effect on Budget, Budget Planning has a insignificant effect on Budget Absorption, Budget Planning is unable to significantly mediate the influence of SPIP, Organizational Commitment is unable to moderate the significant influence of SPIP on the Budget Absorption of the Regional Apparatus Organization of West Halamahera Regency.